Renal Function Mediates the Association Between Klotho and Congestive Heart Failure Among Middle-Aged and Older Individuals - Zhu, Xu; Lu, Xinyi; Yin, Ting; Zhu, Qingqing; Shi, Shi; Cheang, Iokfai; Yue, Xin; Tang, Yuan; Liao, Shengen; Zhou, Yanli; Zhang, Haifeng; Li, Xinli; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Using a newly released National Health and Nutrition Examination Survey (NHANES) data of serum Klotho protein, this study aimed to explore the relationship between Klotho protein and specific cardiovascular diseases (CVD), as well as the mediation effect of renal function, among middle-aged and older individuals within the general population. Methods: This nationally representative cross-sectional study analyzed data from the 2007–2016 NHANES. A total of 13,765 participants, who aged 40 years or older, from the general population were examined. The associations among Klotho protein (exposure), congestive heart failure (CHF; outcome), and renal function markers [estimated glomerular filtration rate (eGFR), blood urea nitrogen (BUN), uric acid (UA), and urine albumin-to-creatinine ratio (UACR); mediators] were investigated using mediation analysis. Results: In comparison to the lowest quartile, Klotho protein in the highest quartile was independently associated with the prevalence of CHF (OR 0.59; 95% CI 0.46–0.77, p for trend = 0.001), but not with other individual CVDs. Klotho had a significant direct effect on the prevalence of CHF (all p < 0.001), while eGFR, BUN, UA, and UACR partly mediated the indirect effect of Klotho protein on the prevalence of CHF (all p < 0.05), explaining 19.51%, 6.98%, 13.93%, and 0.71% of the association between Klotho protein and CHF, respectively. Additionally, restricted cubic spline regression demonstrated a linear association and negative correlation between Klotho protein level and CHF. Conclusions: These findings suggest that Klotho protein is closely linked to CHF and renal function may be a key mediator of this association.